YEAR-TO-YEAR VARIATIONS OF THE HORIZONTAL OZONE DISTRIBUTIONS IN THE NORTHERN HEMISPHERE WINTER - カワヒラ, コウジ; ワカシマ, マサヒロ; KAWAHIRA, Kohji; WAKASHIMA, Masahiro (National Institute of Polar Research, 1995)
P(論文) In order to research a link of the recent rapid ozone depletion to the circulation in the stratosphere and troposphere in the Northern Hemisphere (NH) winter, the horizontal total ozone distributions, given from the observations by Nimbus 7/TOMS (ver. 6), are analyzed by Fourier decomposition along latitude circles in middle latitudes from 1978 to 1991. The results show that the increase (decrease) in the monthly and zonal mean ozone amount in December at 45,50 and 55°N has accompanied the decrease (increase) in the amplitudes of zonal wavenumber 1 and the increase (decrease) of wavenumbers 2 and 3. Further, the comparison of the year-to-year variation between the ozone amount amplitudes and the geopotential height amplitudes clearly indicate positively correlated changes for wavenumbers 1～5. The link of geopotential height wave between the stratosphere and troposphere has also been clearly shown : Year-to-year variations of the amplitudes at 100,500 and 850hPa levels are similar to each other for wavenumbers 1～5. The results suggest the intimate relation of recent ozone depletion in the NH winter to a circulation change in the stratosphere and troposphere. departmental bulletin paper